Biochemical properties and antimicrobial susceptibility pattern of Rothia mucilaginosa isolated from patients with respiratory tract infections (Bangladesh Journal of Medical Science, 2023)
Background: Rothia mucilaginosa is appearing as an alarming pathogen for respiratory tract infection, infection of prosthetic devices and endocarditis. Over the past few years, Rothia sp. are frequently identified in a tertiary hospital of northern Bangladesh. Biochemical properties and antibiotic susceptibility pattern of the isolates were determined.Methods: A total 22 isolates of R. mucilaginosa were studied to observe the fermentation status of carbohydrate and protein substrates for identification by using BD Phoenix M50 system. Antibiotic susceptibility was tested by disk diffusion method.Results: All isolates of R. mucilaginosa showed variable reaction to almost 50% of the carbohydrate and around 50% of protein- amino acid substrates used. Amikacin, meropenem, imipenem and moxifloxacin showed maximum sensitivity in vitro.Conclusion: Biochemical characteristics of R. mucilaginosa can reveal the vital information necessary for accurately identifying the organism within a sample. This depends on production of various enzymes by the organism. Antibiotic susceptibility test is essential for proper management of patient.Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 827-832